2022
DOI: 10.1007/s10529-022-03238-x
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic and conserved peptides from diverse Helicobacter pylori antigens

Abstract: Since the revolutionary finding of Helicobacter pylori as a common bacterial infection, that a high research effort for its eradication has been conducted. Epitope based-vaccine presents advantages over protein-based, as they can be designed to contain epitopes from diverse proteins, therefore, more easily representing the immune-variability of the bacterial population, while minimizing the toxicity associated to some whole proteins. In the present work, an iterative method, to design an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…To learn the potential impact of the L452R and T478K mutations on the RBD antigenicity, we utilized the Jameson and Wolf algorithm 33 , 34 to calculate their antigenic indices, which could generate surface contour profiles and quantitatively predict protein antigenicity from the amino acid sequence. Bioinformatic analyses of the RBD sequences revealed that both L452R and T478K mutations seem to benefit RBD antigenicity, raising the antigenic index values from −0.45 for L452 to −0.15 for R452 and from 0.45 for T478 to 2.05 for K478, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To learn the potential impact of the L452R and T478K mutations on the RBD antigenicity, we utilized the Jameson and Wolf algorithm 33 , 34 to calculate their antigenic indices, which could generate surface contour profiles and quantitatively predict protein antigenicity from the amino acid sequence. Bioinformatic analyses of the RBD sequences revealed that both L452R and T478K mutations seem to benefit RBD antigenicity, raising the antigenic index values from −0.45 for L452 to −0.15 for R452 and from 0.45 for T478 to 2.05 for K478, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To develop successful multi-epitope antigens, at first, the present study carefully selected immunodominant H. pylori PSA D15 and Cag11 proteins which are the major virulence and invasive factors in H. pylori infection, which deserve to be further explored in terms of immunogenic epitopes [6]. According to [33], identification of the conserved region of PSA D15 and Cag11 antigen of H. pylori strains is a critical step for designing a universal epitope-based biomarker/antigens to all H. pylori strains for immunodiagnostic assay development and vaccine design.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that immunity against H. pylori induced by a single antigen does not produce effective protection, and effective immunity against H. pylori infection is often achieved by the combination of various antigens. 197 Therefore, many research groups are committed to developing H. pylori vaccines based on multiple antigens. Epitope-based vaccines are more cost-effective than mixed proteins and can cover more protein targets, so multiepitope vaccines receive more attention.…”
Section: Discussionmentioning
confidence: 99%